Surgery versus 5% imiquimod for nodular and superficial basal-cell carcinoma: five year results of the SINS randomised controlled trial - Williams, Hywel C.; Bath-Hextall, Fiona; Ozolins, Mara; Armstrong, Sarah J.; Colver, Graham B.; Perkins, William; Miller, Paul S.J. (Elsevier, 2016)
Background: We previously reported modest clinical 3-year benefit for topical imiquimod compared with surgery for superficial or nodular basal cell carcinoma (sBCC, nBCC) at low risk sites in our non-inferiority randomised controlled SINS trial. Here we report 5-year data. Methods: Participants were randomised to imiquimod 5% cream once daily (sBCC, 6 weeks; nBCC, 12 weeks) or excisional surgery (4 mm margin). Primary outcome was clinical absence of initial failure or signs of recurrence at 3 year dermatology review. Five year success was defined as 3 year success plus absence of recurrences identified through hospital, histopathology and general practitioner records. Results: Of 501 participants randomised, 401 contributed to the modified intention-to-treat analyses at year 3 (primary outcome), 383 (96%) of whom had data at year 5. Five year success rates for imiquimod were 82·5% (170/206) compared to 97·7% (173/177) for surgery (relative risk of imiquimod success 0·84, 95% CI 0·77 to 0·91, p<0.001). These were comparable to year 3 success rates of 83·6% (178/213) and 98.4% (185/188), for imiquimod and surgery, respectively. Most imiquimod treatment failures occurred in year one. Interpretation: Although surgery is clearly superior to imiquimod, this study shows sustained benefit for lesions that respond early to topical imiquimod.